Superparamagnetic Iron Oxide (Fe_3O_4) Nanoparticles Coated with PEG/PEI for Biomedical Applications: A Facile and Scalable Preparation Route Based on the Cathodic Electrochemical Deposition Method - Karimzadeh, Isa; Aghazadeh, Mustafa; Doroudi, Taher; Ganjali, Mohammad Reza; Kolivand, Peir Hossein (Advances in Physical Chemistry, 2017)
Cathodic electrochemical deposition (CED) is introduced as an efficient and effective method for synthesis and surface coating of superparamagnetic iron oxide nanoparticles (SPIONs). In this way, bare Fe3O4 nanoparticles were electrosynthesized through CED method from aqueous solution Fe3+ : Fe2+ chloride (molar ratio of 2 : 1). In the next step, the surface of NPs was coated with polyethyleneimine (PEI) and polyethylene glycol (PEG) during the CED procedure, and PEG/PEI coated SPIONs were obtained. The prepared NPs were evaluated by powder X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), dynamic light scattering (DLS), vibrating sample magnetometer (VSM), and field-emission scanning electron microscopy (FE-SEM). The pure magnetite phase and nanosize (about 15 nm) of the prepared NPs were confirmed by XRD and FE-SEM. The presence of two coats (i.e., PEG and PEI) on the surface of electrosynthesized NPs was proved via FTIR results. The percentage of polymer coat (37.5%) on the NPs surface was provided by TGA analysis. The high magnetization value, negligible coercivity, and remanence measured by VSM indicate the superparamagnetic nature of both prepared NPs. The obtained results confirmed that the prepared Fe3O4 nanoparticles have suitable physicochemical and magnetic properties for biomedical applications.